Contributions of Classical and New Developmentalism - LUIZ CARLOS BRESSER-PEREIRA (Brazilian Journal of Political Economy)
ABSTRACT In this paper I present the main contribution of classical developmentalism and new developmentalism to economics and political economy. These theoretical frameworks are complementary, not competitive, thus I don’t compare them, I only express a few critiques of one to the other theory. In the case of new-developmental theory, the contributions to economics are presented step by step. The paper rejects the usual critique that it is conservative; on the contrary, it is progressive adopting the well-known tools to achieve the reduction of inequality.